Effect Use of Two Chemical Compounds Sodium Nitrate and Sodium Silicate as Corrosion Inhibitor to Steel Reinforcement - Sarah kareem Mohammed (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
Corrosion of steel reinforcement is one of the biggest problems facing all countries in the world like bridges in the beach area and marine constructions which lead to study these problems and apply some economical solutions. According to the high cost of repair for these constructions, were studied the effect of using kind of chemical compounds sodium nitrite(NaNO2) and sodium silicate(Na2SiO3) as corrosion inhibitors admixture for steel bars that immersed partially in electrolyte solution (water + sodium chloride in 3% conc.) (Approximately similar to the concentration of salt in sea water). The two inhibitors above added each one to the electrolyte solution at concentrations (0.5%, 1% and 2%) for both of them.